Alcohol Consumption, Beverage Preference, and Diet in Middle-Aged Men from the STANISLAS Study - Bernard Herbeth; Anastasia Samara; Maria Stathopoulou; Gérard Siest; Sophie Visvikis-Siest (Journal of Nutrition and Metabolism)
The question about differences in dietary patterns associated with beer, wine, and spirits is still unresolved. We used diet data from 423 middle-aged males of the STANISLAS Study. Using adjusted values for covariates, we observed a negative significant association between increasing alcohol intakes and the consumption of milk, yogurt, and fresh/uncured cheese, sugar and confectionery, vegetables and fruits, and a significant positive relationship with cheese, meat and organs, pork-butcher's meat, and potatoes. In addition, the first dietary pattern identified by factor analysis (characterized a more prudent diet) was inversely related to alcohol intakes. Conversely, when analyzing daily consumption of specific food groups and diet patterns according to beverage preference (wine, beer, and spirits), no significant difference was observed. In conclusion, in this sample of middle-aged French males, there was a linear trend between increasing alcohol intakes and worsening of quality of diet, while no difference was observed according to beverage preference.